Penentuan Strategi Pengembangan Usaha Pada Bidan Praktek Mandiri (BPM) Dengan Analisis Porter Five Force Dan SWOT - Suwiyanti , Retno; Sulastri , Sulastri; Anggraeni , S. Tiwi (Politeknik Negeri Ambon, 2024)
This scientific research aims to determine the strength of Mrs. BPM. Sukami in facing weaknesses and threats based on SWOT analysis and Porter's Five Forces analysis and determining Mrs. Sukami's BPM strategy. Sukami in utilizing existing strengths and opportunities to develop his business. The data collection methods used were interviews, observation and documentation. The factors analyzed in this paper include main competition, threat of new entrants, threat of substitute services, buyer power analysis, and supplier power analysis. Then carry out an analysis of Porter's five forces which includes the data classification stage, carrying out a SWOT analysis and then the results of the analysis are developed for strategic decision making. The results of the analysis of the five strengths with the highest weight are main competitors, the threat of new BPM and the threat of substitute health facilities, while supplier strength and patient strength are low in weight. Keywords: Business Development Strategy, Porter's Five Forces Analysis, SWOT Analysis